Pendampingan dan Pelatihan Pengajaran Geomatika Menggunakan Perangkat Simusurveyx dan Stake Out Guide di Program Keahlian Geospasial dan Geologi Pertambangan SMKN 1 Balikpapan - Mariatul Kiptiah; Totok Sulistyo; Karmila Achmad; Fatmawati Fatmawati; Desak Made Ristia Kartika (Abdimas Universal, 2022)
The Geospatial and Mining Geology Expertise Program at SMKN 1 Balikpapan has limitations in terms of facilities and infrastructure, the workshop building uses a former automotive workshop building which is not sufficiently representative as other skill program workshops. In terms of Geomatics practice equipment, two skill programs with resource sharing with very minimal facilities, where the equipment owned are as follows: 3 units of PPD, 1 unit of Digital Theodholite, and 2 units of TS where 1 battery unit is damaged, not proportional to the number of students with geospatial skills as many as 165 people with 6 teachers and 248 skill students with 8 teachers being less than optimal during geomatics practice. The assistance and training of the simulation tool survey and stake out guide carried out by the PkM Poltekba team is an alternative tool for the teaching and learning process in the field of measurement, making it easier for teachers and students to facilitate basic measurements and surveys in the field and reduce the risk of using limited tools so that the teaching and learning process becomes more optimal.